2021
DOI: 10.33711/yyuefd.859490
|View full text |Cite
|
Sign up to set email alerts
|

Yenilenen İlköğretim Matematik Öğretmenliği Lisans Programı İle İlgili Öğretim Elemanlarının Görüşleri

Abstract: The aim of this study is to evaluate the elementary mathematics teacher undergraduate program, which started to be implemented as of the 2018-2019 academic year, in line with the opinions of the lecturers. The participants of the study, in which a qualitative research approach was adopted and designed with a holistic single case study design, are 12 lecturers working in the department of mathematics education at a state university in the Eastern Anatolia Region. In the study, a semi-structured interview form d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 14 publications
(4 reference statements)
2
5
0
1
Order By: Relevance
“…This emphasis aligns with studies advocating for teaching innovation to increase student engagement, such as Basturk (2009Basturk ( , 2010, Budak et al (2011), and Uzun and Koparan (2021). However, studies including Cetin et al (2021), Demir et al (2021), and Uzun and Koparan (2021) identified inadequate integration of technology in teacher training programs, suggesting the need for program updates. Particularly, Uzun and Koparan (2021) emphasized the importance of supporting lessons with educational games, Web 2.0 tools, dynamic software, interactive boards, and other technologies.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 60%
See 2 more Smart Citations
“…This emphasis aligns with studies advocating for teaching innovation to increase student engagement, such as Basturk (2009Basturk ( , 2010, Budak et al (2011), and Uzun and Koparan (2021). However, studies including Cetin et al (2021), Demir et al (2021), and Uzun and Koparan (2021) identified inadequate integration of technology in teacher training programs, suggesting the need for program updates. Particularly, Uzun and Koparan (2021) emphasized the importance of supporting lessons with educational games, Web 2.0 tools, dynamic software, interactive boards, and other technologies.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 60%
“…Critiques from academics concerning the inadequacy of time and credits allocated to field knowledge courses, and reservations about completing these courses within the stipulated periods, were tempered by a positive view of the updated curriculum. Cetin et al (2021) corroborated the findings of Demir et al (2021), asserting that the revision of the teacher training undergraduate program was not solely driven by political motives, but rather aimed at addressing deficiencies in training qualified teachers and rectifying inadequacies stemming from the preceding program. They contended that the overarching goal of the update was to produce teachers who are suited to contemporary needs, pedagogically adept, socially, culturally, and philosophically developed, with augmented professional knowledge and skills.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Ayrıca akademisyenlerin görüşlerinden elde edilecek verilerin 2020 yılında gerçekleşen değişiklikle ders kategorileri (Alan Eğitimi Dersleri, Öğretmenlik Meslek Bilgisi Dersleri ve Genel Kültür Dersleri) ders sayısı, ders saati/kredi sayısı ve yoğunluğu aynı kalmak şartıyla yükseköğretime kurumlarına bırakılan "öğretmenlik programlarındaki derslerin, müfredatların ve kredilerin belirlenmesine rehberlik etmesi beklenmektedir. Alanyazın incelendiğinde 2018 yılında uygulamaya konulan lisans programları ile daha önceki yıllarda uygulanan lisans programlarının bazı bölümler kapsamında karşılaştırıldığı (Akarsu, Yılmazer ve Geçit, 2020;Sağdıç, 2018), 2018 lisans programlarının bazı bölümleri akademisyen görüşleri bağlamında incelendiği (Ağçam ve Babanoğlu, 2020;Aykaç ve Stebler, 2019;Dağtekin ve Zorluoğlu, 2019;Demir, Akbaş ve Gök, 2021) görülmüştür. Ancak 2018 öğretmen yetiştirme lisans programlarının bütünsel bir bakış açısı ile ele alınmadığı görülmüştür.…”
Section: Introductionunclassified
“…Ignoring the opinions of the people who are the implementers of the programme, besides the failure of the change, also causes loss of money, time and energy (Ornstein and Hunkins, 2014). When the literature is examined, it is seen that the undergraduate programmes implemented in 2018 and in previous years are compared within the scope of some departments (Akarsu et al, 2020;Sagdic, 2018;Yucetoker, 2019), in which some parts of the 2018 undergraduate programmes were examined in the context of the opinions of academics (Agcam & Babanoglu, 2020;Aykac & Stebler, 2019;Dagtekin & Zorluoglu, 2019;Demir et al, 2021).…”
Section: The Structure Of Piano Lessons In Music Education Undergradu...mentioning
confidence: 99%